TEACHING MULTIPLICATION OF NUMBERS FROM 1 TO 10 TO STKIP SURYA STUDENTS USING MATEMATIKA GASING - Josephine Kusuma; Sulistiawati Sulistiawati (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
Multiplication of numbers from 1 to 10 is very important as it provides the basis for learning multiplication of other larger numbers as well as other related mathematical operations. How do students learn multiplication? Usually students just memorize the results of multiplication. This is often performed without a complete comprehension of the concept of multiplication. This study aimed to discuss how to teach multiplication of numbers from 1 to 10 to STKIP Surya students using Matematika GASING. GASING stands for Gampang, ASyIk dan menyenaNGkan which is translated as easy, fun and enjoyable. The materials are taught according to its unique way of teaching mathematics which follows three stages: concrete, abstract and mental calculation. The first stage (concrete) encourages students to explore using concrete objects. This is done prior to the second stage called the abstract stage. Students are then able to move on to the third stage where they can do mathematical calculation mentally and instantly. By following these stages in this order, students can understand mathematics more easily and clearly. The research method used in this study was design research. It consists of three phases; they are preliminary design, teaching experiment and retrospective analysis.The sample was fourteen first-year undergraduate students (matriculation level) at STKIP Surya (Surya College of Education), Tangerang, Banten. The instruments used were both oral and written tests. They were used to measure the ability of performing mental computation as well as the ability to teach this material. This study showed that Matematika GASING helpedthese students to understand and be able to teach multiplication of numbers from 1 to 10 better.Keywords: multiplication of numbers from 1 to 10, Matematika GASING, design research DOI: http://dx.doi.org/10.22342/jme.5.1.1450.66-84